1988
DOI: 10.1002/ajmg.1320290320
|View full text |Cite
|
Sign up to set email alerts
|

Parental decision following prenatal diagnosis of fetal chromosome abnormality

Abstract: In the event of prenatal diagnosis of fetal chromosome abnormality, parents must choose between continuation and termination of the pregnancy. To determine whether parents are capable of understanding differences in severity among aneuploidy syndromes, we examined the outcome chosen for all pregnancies in which a fetal chromosome disorder was diagnosed at Northwestern Memorial Hospital between January, 1977 and June, 1986. Among amniocentesis cases, 88% with autosomal aneuploidy were terminated, but only 41% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 35 publications
(13 reference statements)
6
53
1
5
Order By: Relevance
“…Table 2 and Table 3 show the details of terminated cases. other authors have shown that the termination rates are highest following a prenatal diagnosis of Down syndrome and lowest following diagnosis of Klinefelter syndrome (3,4,5,10,11,13,19). our results are in concordance with prior findings of an increased rate of termination in the case of a more severe prognosis (e.g.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Table 2 and Table 3 show the details of terminated cases. other authors have shown that the termination rates are highest following a prenatal diagnosis of Down syndrome and lowest following diagnosis of Klinefelter syndrome (3,4,5,10,11,13,19). our results are in concordance with prior findings of an increased rate of termination in the case of a more severe prognosis (e.g.…”
Section: Resultssupporting
confidence: 92%
“…autosomal trisomy) compared with that for abnormal karyotypes with a less severe prognosis (e.g. sex chromosome aneuploidy) (3,4,5,10,11,13,19).…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive data: Type of SCA represented the most frequent factor associated with terminating a pregnancy, identified in more than half of the reviewed studies (57.9%). 3,[8][9][10]18,20,22,23,[27][28][29] Two specific types of SCAs, 45,X (Turner syndrome) and 47,XXY (Klinefelter syndrome), in particular, were associated with termination. Nine studies (47.4%) [8][9][10]18,20,23,[27][28][29] indicated that parents with a Turner syndrome-affected fetus would be more likely to terminate the pregnancy, with an average termination rate of 76% (range: 33-100%).…”
Section: Studies' Findingsmentioning
confidence: 99%
“…Nine studies (47.4%) [8][9][10]18,20,23,[27][28][29] indicated that parents with a Turner syndrome-affected fetus would be more likely to terminate the pregnancy, with an average termination rate of 76% (range: 33-100%). Seven studies (36.8%) 3,[8][9][10]18,20,22 reported a diagnosis of Klinefelter syndrome led parents to decide to terminate the pregnancy, yielding an average termination rate of 61% (range: 44-85%). As an example, a study conducted by Sagi et al 20 examined 60 cases from patient records in the 10 years between 1989 and 1998 and identified that all five pregnancies (100%) exhibiting 45,X (Turner syndrome) and 85% (n = 7) with 47,XXY (Klinefelter syndrome) were terminated.…”
Section: Studies' Findingsmentioning
confidence: 99%
“…In these cases, about 60-90% of parents choose to terminate the pregnancy after receiving the diagnosis of the abnormality. [22][23][24] In Brazil, the current legislation does not provide permission for termination of a pregnancy in cases of chromosomal abnormalities, and this practice is typified in the country's Criminal Code. There are favorable judicial decisions for termination in the case of anomalies incompatible with life.…”
Section: Introductionmentioning
confidence: 99%